A Linguistic Analysis of Humor Found in It Crowd Sitcom - Annisha Dyuli Adha; Dwi Megista Putri; Rasmita Rasmita (Jurnal Ilmiah Langue and Parole, 2022)
This study aims to analyze the Semantic Mechanism of Humor in the IT Crowd sitcom, and also to find out the deviations of the linguistic elements contained in the humor. In this study, the sources of data were humorous dialogues contained in the IT Crowd sitcom using descriptive methods. The results of the study show that the linguistic elements found in all the conversations in the sitcom including lexical ambiguity (LA), causal fallacy (CF), presupposition (Pr), locutionary (Lc), and topic progression (TP). In addition, a semantic mechanism of humor is also needed in this study because from this mechanism one can understand what causes humor to be funny. After understanding this mechanism, then we can know what linguistic expectations deviations are contained in the humor, and research shows that most humor occurs due to the appearance of unexpected meaning [M2] from what is expected [M1].